2013
DOI: 10.1039/c3cp53079e
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for solvent dependent morphologies observed on electrosprayed surfaces

Abstract: We study the causes of the observed tunable hydrophobicity of poly(styrene-co-perfluoroalkyl ethylacrylate) electrosprayed in THF, DMF, and THF : DMF (1 : 1) solvents. Under the assumption that equilibrium morphologies in the solvent significantly affect the patterns observed on electrosprayed surfaces, we use atomistic and coarse-grained simulations supported by dynamic light scattering (DLS) experiments to focus on the parameters that affect the resulting morphology of superhydrophobic electrosprayed beads. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…This indicates that the population giving the second peak at over 100 nm in the intensity-based distribution is small. The second peak in the intensity-based distribution can be attributed to agglomerated polymer chains due to lack of swelling in water . It is also observed that although all the PMSEA–PTFEA polymers have comparable molecular weights, the size of these polymers in aqueous solution increased with increasing fluorine content.…”
Section: Resultsmentioning
confidence: 92%
“…This indicates that the population giving the second peak at over 100 nm in the intensity-based distribution is small. The second peak in the intensity-based distribution can be attributed to agglomerated polymer chains due to lack of swelling in water . It is also observed that although all the PMSEA–PTFEA polymers have comparable molecular weights, the size of these polymers in aqueous solution increased with increasing fluorine content.…”
Section: Resultsmentioning
confidence: 92%
“…THF : THF displays an anomaly compared to all other antisolvents. The precursor solution does not precipitate but disperses in THF, which is likely caused by the molecular repulsion between THF and DMF . As a result, crystal growth is stunted with THF treatment, which leads to the smallest grain size as well as smallest crystallite size for THF‐treated films samples (Figure a and Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In this process, MoO 3 aqueous droplets are continuously deposited, but the low vapor pressure of the additive solvent causes organic solvent to remain on the substrate after depositing the droplet. E. Ozden-Yenigun demonstrated that the drying process of the thin film was influenced by (i) the boundary layer resistance to solvent transport into vapor and (ii) the internal diffusion resistance to solvent loss [46] . In addition, the slow evaporation speed of the droplet occurs the main resistance to solvent loss, resulting in the free movement of solvent in the droplet.…”
Section: Resultsmentioning
confidence: 99%